KONTRIBUSI MODERASI BERAGAMA DALAM MEWUJUDKAN TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS) DI INDONESIA - Muntoha, Tohir (LPPM STAI Muhammadiyah Probolinggo, 2025)
Indonesia, as a country with rich religious, ethnic and cultural diversity, faces challenges in achieving the Sustainable Development Goals (SDGs). One important aspect in addressing these challenges is religious moderation, which can play a key role in creating social peace and justice. This study aims to explore the contribution of religious moderation in realizing the SDGs in Indonesia, especially in creating social harmony, improving the quality of education, and reducing social inequality. The research method used is a qualitative approach with a literature study, which involves analyzing various sources of journals, books, and policy reports related to religious moderation and the SDGs. The research findings show that religious moderation plays a significant role in creating a more just society, reducing social tensions between religious groups, and increasing social empowerment through inclusive education. The results provide insight into the importance of integrating religious moderation in public policy to achieve more inclusive and sustainable SDGs.